Board Game Media Increased Elementary Student Learning Motivation: Media Permainan Papan Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Roichatul Jannah; Tri Linggo Wati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Learning motivation plays a central role in determining student participation and achievement in primary education settings. Specific Background Classroom observations revealed that many elementary students showed low enthusiasm, limited engagement, and passive behavior during lessons due to the lack of varied instructional media. Knowledge Gap Although numerous studies discuss learning media, the use of educational board game–based media to stimulate motivation in this specific classroom context has not been widely implemented. Aims This study aimed to examine the use of board game learning media to increase students’ learning motivation in elementary classrooms. Results The findings indicated higher student participation, more active interaction, greater enthusiasm, and improved motivation scores after the implementation of the game-based activities compared with the initial condition. Novelty The study introduces a structured integration of traditional board game mechanics into classroom instruction as an engaging pedagogical strategy. Implications These results suggest that game-based media can be adopted by teachers as a practical alternative to create interactive, student-centered, and motivating learning environments in primary schools. Keywords : Board Game Media, Learning Motivation, Elementary Students, Game Based Learning, Classroom Engagement Key Findings Highlights : Students demonstrated stronger classroom participation Interactive play encouraged collaborative behavior Motivation scores showed consistent upward change